Applying augmented reality for experiential learning: a case study of E-Commerce Learning - Huang, Hsiu-Mei (International Dialogues on Education Journal, 2015)
The great impacts of advancing technology, such as 3D virtual worlds, create new learning opportunities for learners. Educators and researchers have been exploring how to apply 3D virtual technology to improve the virtual learning process and authentic activities. Augmented reality (AR) technology offers the opportunity for learners to interact in both the virtual and real world significantly. Augmented reality can be an attractive technology that allows learners to realize that virtual and real objects coexist at the same time. Therefore, AR technology allows educators to design courses utilizing simulation, visualization, and interaction with the virtual objects and real environments. For Dewey (1916), learning should be real and applicable to daily living. This study builds an e-commerce learning system based upon Kolb’s experiential learning theory.